2018
DOI: 10.3389/fimmu.2018.02810
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Resident CD8 Memory T Cell Responses in Cancer and Autoimmunity

Abstract: Resident memory (TRM) cells are a distinct tissue-localized T cell lineage that is crucial for protective immunity in peripheral tissues. While a great deal of effort has focused on defining their role in immunity to infections, studies now reveal TRM cells as a vital component of the host immune response to cancer. Characterized by cell-surface molecules including CD103, CD69, and CD49a, TRM-like tumor-infiltrating lymphocytes (TILs) can be found in a wide range of human cancers, where they portend improved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 163 publications
3
62
0
Order By: Relevance
“…Trm cells produce higher amounts of cytokines than their circulating counterparts and provide enhanced local immunity in response to infection (12,13). CD8 þ Trm cells are associated with antitumor immune responses (14,15). The presence of Trm cells correlates with improved prognosis in patients with cancer (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Trm cells produce higher amounts of cytokines than their circulating counterparts and provide enhanced local immunity in response to infection (12,13). CD8 þ Trm cells are associated with antitumor immune responses (14,15). The presence of Trm cells correlates with improved prognosis in patients with cancer (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…T he induction of CD8 tissue-resident memory T cells (Trm) in the lung following respiratory infection is an integral component of front-line mucosal defense against future pathogen exposure (1-5). However, the mechanism of lung Trm differentiation and commitment remains unclear (1,2,6,7). It was recently demonstrated that the TNFR superfamily member 4-1BB provides a critical signal for the establishment of influenzaspecific lung-resident memory T cells, as measured at day 30 postinfection in the lung (8).…”
mentioning
confidence: 99%
“…Among TILs, T resident-memory (T RM ) cells are permanent tissue-resident T cells able to mount an immune reaction; they've been proposed to be key determinants in the magnitude of antitumor immune responses, and their presence in different human cancers correlates with survival (329)(330)(331)(332)(333)(334)(335)(336). It is tempting to assume that the induction and/or manipulation of this T cell subset might improve anti-tumor immunity and disease control.…”
Section: Generating Genetically Engineered T Resident-memory Cellsmentioning
confidence: 99%